2019
DOI: 10.11648/j.ijhnm.20190501.17
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breast Feeding Prevalence and Associated Factors an Institutional Based Cross Sectional Study in Bahir dar Northwest Ethiopia

Abstract: Exclusive breastfeeding is accepted as the best natural form of infant feeding up to six months and has a protective effect against morbidity and mortality. The objective of this study is to assess the prevalence of exclusively breastfeeding and associated factors during the first six months among mothers who was attending in Bahir Dar public health centers and private pediatric clinics. An institutional based cross-sectional study was conducted on mothers with infants sixtwelve months of age. Multi-stage samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…From nine regions of Ethiopia, seven regions and two council cities were represented in this meta-analysis. Fifteen of the studies were from Amhara [ 33 42 , 58 , 59 , 75 77 ] two from Addis Ababa [ 64 , 73 ], four from Affar [ 34 , 56 , 57 , 74 ] four from Oromia [ 44 , 60 , 61 , 80 ], twelve from SNNP [ 45 – 47 , 62 – 65 , 67 70 , 72 ], one from Tigray [ 71 ], two from Somalia [ 48 , 79 ], two from Harari [ 43 , 78 ], one from nationwide [ 49 ], one from Diredawa [ 50 ] and one from SNNP and Tigray [ 81 ]. No studies were reported from Benishangul Gumiz and Gagmbela in this review research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From nine regions of Ethiopia, seven regions and two council cities were represented in this meta-analysis. Fifteen of the studies were from Amhara [ 33 42 , 58 , 59 , 75 77 ] two from Addis Ababa [ 64 , 73 ], four from Affar [ 34 , 56 , 57 , 74 ] four from Oromia [ 44 , 60 , 61 , 80 ], twelve from SNNP [ 45 – 47 , 62 – 65 , 67 70 , 72 ], one from Tigray [ 71 ], two from Somalia [ 48 , 79 ], two from Harari [ 43 , 78 ], one from nationwide [ 49 ], one from Diredawa [ 50 ] and one from SNNP and Tigray [ 81 ]. No studies were reported from Benishangul Gumiz and Gagmbela in this review research.…”
Section: Resultsmentioning
confidence: 99%
“…This regional variation might be because of differences in socio-demographics, and the difference in numbers of the studies included in the two regions during analysis. In addition to the above, the participants of a study conducted in SNNP and Tigray region were rural resident mothers, and according to different kinds of literature being rural in residence for breastfeeding mothers is associated with a high prevalence of EBF practice [ 66 , 77 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the full texts of 54 articles were reviewed comprehensively, of which 42 articles [ 8 , 9 , 20 – 59 ] were found eligible to the current study. Nine articles were excluded after the full text review, due to inconsistent reports [ 60 64 ] and incomplete results [ 64 69 ]. Of the total articles included to this study, 24 articles were eligible to pooled estimates of the effect of employment status on the EBF practice of women in Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the studies were from Amhara [34][35][36][37][38][39][40][41][42][43]55,68,116,117,119], two from Addis Ababa [52,53], four from Affar [33,58,63,115], four from Oromia [45,64,65,122], twelve from SNNP [46][47][48]51,52,54,57,59,60,61,62,66], one from Tigray [67], two from Somalia [49,121],two from Harari [44,120],one from nationwide [50],one from Diredawa [118] and one from SNNP and Tigray [123]. No studies reported from Benishangul Gumiz and Gagmbela in this review research.…”
Section: Resultsmentioning
confidence: 99%
“…This regional difference in the prevalence of exclusive breastfeeding might be because of differences in socio-demographic, the difference in numbers of the studies included in the two regions during analysis. In addition to the above, the participants of a study conducted in SNNP and Tigray region are rural resident mothers, and according to different kinds of literature being rural in residence for breastfeeding mothers is associated with a high prevalence of exclusive breastfeeding practice [56,119,125]. We also performed a subgroup analysis using a year of study publication.…”
Section: Discussionmentioning
confidence: 99%